2000
DOI: 10.5194/aab-43-327-2000
|View full text |Cite
|
Sign up to set email alerts
|

Liegeverhalten von Pferden in Gruppenauslaufhaltung

Abstract: SummaryTitel of the paper: Recumbence resting behaviour of horses in loose housing Systems with open yards Recumbence resting behaviour was investigated in 48 horses in four loose housing Systems with open yards subdivided in areas for feeding, recumbence and for free ränge. Continuous observations were made for each loose housing system on three independent days during a 24-hr period. In all housing Systems the horses chose exclusively the area of recumbence to rest in sternal or lateral position. On the one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 2 publications
3
8
1
1
Order By: Relevance
“…Accordingly, individually stabled horses spent more time in lateral position if kept in a larger compared to smaller box stalls ( 58 ). Nonetheless, the model estimates of the proportion of lateral recumbency in the present study were much lower compared to the reported mean ranges of 15–30% in feral horses ( 3 , 28 ) and 4–30% in group-housed horses ( 37 , 40 , 59 , 60 ). If we had not transformed our data, the model estimates of the proportion of lateral recumbency would increase continuously from 6.99% (0.68%, 13.3%) in treatment T0 to 9.07% (2.84%, 15.3%) in T0.5, 11.14% (5.03%, 17.26%) in T1, and 13.22% (6.93%, 19.51%) in T1.5; and would therefore have met the mean ranges in the literature.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Accordingly, individually stabled horses spent more time in lateral position if kept in a larger compared to smaller box stalls ( 58 ). Nonetheless, the model estimates of the proportion of lateral recumbency in the present study were much lower compared to the reported mean ranges of 15–30% in feral horses ( 3 , 28 ) and 4–30% in group-housed horses ( 37 , 40 , 59 , 60 ). If we had not transformed our data, the model estimates of the proportion of lateral recumbency would increase continuously from 6.99% (0.68%, 13.3%) in treatment T0 to 9.07% (2.84%, 15.3%) in T0.5, 11.14% (5.03%, 17.26%) in T1, and 13.22% (6.93%, 19.51%) in T1.5; and would therefore have met the mean ranges in the literature.…”
Section: Discussioncontrasting
confidence: 96%
“…If litter was available, increasing dimensions of the littered area resulted in increased durations of recumbency. In accordance therewith, previous studies also found a positive correlation between the duration of recumbency and the space allowance of the littered area, i.e., a lower total duration of recumbency in group-housed horses with smaller space allowances of the littered area compared to group-housed horses with larger dimensions at their disposal ( 35 , 37 ). With regard to the legally required minimal dimensions for the littered area in Switzerland ( 43 , 44 ), a reduction in the dimensions of the littered area from treatment T1 to T0.5 caused a decrease in the durations of recumbency both in total and on litter as well as a higher probability for an individual to be recumbent for less than 30 min per 24 h on litter.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations